ANALISIS PENGASUHAN AYAH PADA REALITY SHOW THE RETURN OF SUPERMAN - Neni Mulya; Sekar Eka Febriani (Jurnal Panrita, 2024)
This study aims to analyse the parenting of fathers on the reality show "The Return of Superman" This research is a qualitative study that uses the type of Library Research. The data sources used in this study are primary data sources, namely Reality Show The Return of Superman and secondary data sources in the form of books and journals. The data collection technique uses the documentation method from the Reality Show The Return of Superman. The technique used to see the validity of the data uses the technique of increasing persistence in research. This research uses data analysis techniques in the form of content analysis of the Reality Show The Return of Superman. The results obtained show that father's parenting in the Reality Show The Return of Superman father as a leader can develop the behaviour of imitation, empathy, and cooperation. Fathers as providers of needs can develop the behaviour of generosity and empathy. Fathers as educators can develop sympathy, cooperation, and friendly behaviour. As a playmate, they can develop cooperation and selflessness. Fathers as problem solvers can develop competitive behaviour.